PENGARUH ORIENTASI KERJA DISIPLIN KERJA DAN TRAINING AND DEVELOPMENT TERHADAP KINERJA TENAGA KEPENDIDIKAN DI SEKOLAH KRISTEN PELITA NUSANTARA KASIH SURAKARTA - Miracle, Fide; Palupi, Dyah Ayu Puri (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
Employee work orientation is a step to introduce new employees to the new environment as well as job descriptions and coworkers. Work discipline is also an achievement in the work environment and training and development will affect the performance of education personnel. This study aims to analyze the effect of work orientation, work discipline and training and development on the performance of education personnel. This type of research is quantitative research with a total sample in this study of 54 people selected based on non-probability sampling techniques (not random) with purposive sampling sample selection techniques, namely educational staff respondents who work at Pelita Nusantara Kasih Christian School Surakarta City, and data collection methods using questionnaires. The results showed that work orientation variables, work discipline variables, training and development simultaneous influenced the performance of educational staff at Pelita Nusantara Kasih Christian School in Surakarta City.